Anti‐ADAMTS13 autoantibodies in immune‐mediated thrombotic thrombocytopenic purpura do not hamper ELISA‐based quantification of ADAMTS13 antigen. (27th February 2020) - Dekimpe, Charlotte; Roose, Elien; Tersteeg, Claudia; Joly, Bérangère S.; Dewaele, Aurélie; Horta, Sara; Pareyn, Inge; Vandenbulcke, Aline; Deckmyn, Hans; Feys, Hendrik B.; Tellier, Edwige; Kaplanski, Gilles; et al.
Abstract: Background: The biological diagnosis of immune‐mediated thrombotic thrombocytopenic purpura (iTTP) is based on determination of ADAMTS13 activity (<10%) and anti‐ADAMTS13 autoantibodies. ADAMTS13 antigen levels are not routinely measured in iTTP patients, but studies have shown that antigen levels are a valuable prognostic factor. Objectives: To (a) report the validation of our in‐house developed ADAMTS13 antigen enzyme‐linked immunosorbent assay (ELISA) and determine ADAMTS13 antigen in a large cohort of healthy donor and iTTP patient plasma samples; and (b) to investigate whether ADAMTS13 antigen determination is not disturbed by the presence of anti‐ADAMTS13 autoantibodies. Methods: Our in‐house ADAMTS13 antigen ELISA was validated in terms of sensitivity, repeatability, and reproducibility. ADAMTS13 antigen levels were determined in plasma samples from 423 healthy donors and 112 acute iTTP patients. Purified IgGs from iTTP patients were added to normal human plasma to determine whether anti‐ADAMTS13 autoantibodies hampered ADAMTS13 antigen determination. Results: Our in‐house ADAMTS13 antigen ELISA has a detection limit of 3% and low intra‐assay (coefficient of variation, %CV < 10%) and inter‐assay (%CV < 18%) variability. ADAMTS13 antigen levels were significantly reduced ( P < .0001) in acute iTTP patients (15 ± 18%) compared to healthy donors (101 ± 18%). The anti‐ADAMTS13 autoantibodies in plasma of iTTP patients did not impede ADAMTS13 antigen determinations using our in‐house ELISA. Conclusions: Our in‐house ADAMT13 antigen ELISA is a powerful tool to correctly determine ADAMTS13 antigen levels in iTTP patients, which supports routine ADAMTS13 antigen measurements in these patients to have better insight into disease prognosis.